PENGARUH KEMIRINGAN TALANG TERHADAP PERTUMBUHAN DAN HASIL DUA VARIETAS PAKCOY (Brassica rapa L.) DENGAN SISTEM HIDROPONIK NUTRIENT FILM TECHNIQUE - Suprayogi, Syahtian; Suprihati, Suprihati (Jurnal Teknik Pertanian Lampung (Journal of Agricultural Engineering), 2021)
The slope of the gutter affects the dissolved oxygen content in the hydroponic nutrient flow. Dissolved oxygen is one of the factors that can affect plant growth and yield. This study aims to determine the effect of gutter slope on the growth and yield of pakcoy plants. The research was conducted at Jl. Pundak Sari, Kutowinangun Kidul, Salatiga, Central Java from March to May 2019 in the greenhouse. Treatment of a combination of green and white pakcoy varieties with a chamfer slope of 6%, 9% and 12%. Each was repeated four times to get 24 experimental units. This study used a randomized block design. The parameters observed were dissolved oxygen, plant height, number of leaves, crown diameter, plant fresh weight. Data were analyzed using variants. To find out the differences between treatments, the DMRT test was used with a 95% confidence interval. Based on the results of the study,bhi the combination of varieties and the slope of the gutter had a significant effect on the number of leaves, crown diameter, and plant fresh weight. The combination of green pakcoy variety with 12% gutter slope gave the best results including plant height 25.32 cm, number of leaves 18.83, crown diameter 33.36 cm and fresh weight of 161.4 g plant-1. Keywords: NFT, varieties, slope gutters, dissolved oxygen